Bacterial culture components activating colorimetric transition in polydiacetylene nanofiber composites - Bhattacharjee, Abhishek, author; Li, Yan Vivian, advisor; Gentry-Weeks, Claudia, committee member; Diddi, Sonali, committee member (Colorado State University. Libraries, 2020)
Polydiacetylene (PDA) demonstrates colorimetric transition behaviors due to conformational changes in π conjugated backbone of PDA macromolecules at external stimuli of bacteria, suggesting potential applications in biosensors. However, the bacterial culture components activating colorimetric transition in PDAs are still undetermined due to the complexity of the bacterial system. In this study, PU-PDA nanofiber composite was prepared via electrospinning and tested with components from Escherichia coli (E. coli) culture including supernatant fluid, cell pellet, and extracellular polymeric substances (EPS). When PU-PDA nanofiber was tested with supernatant fluid, it changed color from blue to red. In contrast, bacterial cell pellets could not induce a color change, suggesting the color-changing substances (CCS) are not cell-associated, rather can be found in the spent media (supernatant fluid) generated by E. coli during its growth phase. Intense color change in the nanofiber by the autoclaved supernatant fluid indicated that the CCS may not be a protein, DNA, or RNA since they denature in high heat and pressure from the autoclaving process. With an increase in storage time of the supernatant fluid, the color-changing rate was reduced significantly, suggesting a degradation in CCS with time. Free EPS from the supernatant fluid could induce a color change in the nanofibers, which confirmed that EPS contains the CCS. No significant changes were found in the morphology of PU-PDA nanofibers before and after the exposure of E. coli culture components. Critical bacterial concentration (CBC) was found approximately 9 × 108 CFU/ml, suggesting the efficiency of the PU-PDA nanofiber composite to be used as a biosensor. Additionally, solvatochromism of the nanofiber composite was investigated using organic solvents commonly used in extracting bacterial culture components. The results from this study provided a guideline for using PU-PDA nanofiber composite as a biosensor in point-of-care applications.
Keywords: colorimetric transition; extra-cellular polymeric substances; polydiacetylene; biosensor; point-of-care; Escherichia coli